2015
DOI: 10.1111/aor.12630
|View full text |Cite
|
Sign up to set email alerts
|

Tooth Germ‐Like Construct Transplantation for Whole‐Tooth Regeneration: An In Vivo Study in the Miniature Pig

Abstract: The purpose of this study was to demonstrate the feasibility of whole-tooth regeneration using a tooth germ-like construct. Dental pulp from upper incisors, canines, premolars, and molars were extracted from sexually mature miniature pigs. Pulp tissues were cultured and expanded in vitro to obtain dental pulp stem cells (DPSCs), and cells were differentiated into odontoblasts and osteoblasts. Epithelial cells were isolated from gingival epithelium. The epithelial cells, odontoblasts, and osteoblasts were seede… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 37 publications
0
10
0
1
Order By: Relevance
“…Angelova Volponi et al reported success using adult gingival epithelial cells, which upon recombination with mesenchymal cells generate mature teeth and form enamel and dentin [137]. Similarly, Yang et al generated a complete tooth by implantation of a tooth germ like structure in animal models [138].…”
Section: Whole Tooth Regenerationmentioning
confidence: 99%
“…Angelova Volponi et al reported success using adult gingival epithelial cells, which upon recombination with mesenchymal cells generate mature teeth and form enamel and dentin [137]. Similarly, Yang et al generated a complete tooth by implantation of a tooth germ like structure in animal models [138].…”
Section: Whole Tooth Regenerationmentioning
confidence: 99%
“…PLLA, PLGA and their derivatives are synthetic polymers that can be readily prepared. Hydrogel based materials such as collagen, gelatin, and alginate are highly tunable, and have been used to successfully bioengineer various dental tissues [21, 22, 32, 52]. Silk-based materials have also shown promise in providing an environment that can support osteo-dentin like mineralized tissue formation, but further optimizations are needed to enhance bioengineered dental tissue formation [53, 54].…”
Section: Scaffold Materials and Bioprinitng For Tooth Tissue Engineeringmentioning
confidence: 99%
“…Decreased FGF signaling prevents tooth development [71, 72]. TGFβ1 can induce odontoblast differentiation, pulp and dentin formation [7376], and has been used to enhance the differentiation DPSCs into odontoblasts in vitro [21]. These studies emphasize that selective incorporation of combinations of these growth factors into novel bioengineered tooth constructs could be used to enhance dental cell differentiation, and dental tissue and whole tooth formation.…”
Section: Incorporation Of Growth Factorsmentioning
confidence: 99%
See 2 more Smart Citations